2017
DOI: 10.1016/j.ceb.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

MyTH4-FERM myosins in the assembly and maintenance of actin-based protrusions

Abstract: Unconventional myosins are actin-based molecular motors that serve a multitude of roles within the cell, contributing to cell shape and function. One group of myosin motors, MyTH4-FERM myosins, plays an integral part in building and maintaining finger-like protrusions, which allows cells to interact with their external environment. Suggested to act primarily as transporters, these motor proteins enrich adhesion molecules, actin-regulatory proteins and other factors at the tips of filopodia, microvilli, and ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 154 publications
3
30
0
Order By: Relevance
“…Myo10 is a member of a phylogenetically ancient group of myosins characterized by one or more MyTH4-FERM domains (Myosin Tail Homology 4 and band 4.1, Ezrin, Radixin, Merlin). The MyTH4-FERM myosins are strongly associated with protrusions based on actin bundles, such as filopodia, microvilli, and inner ear stereocilia 10 , 11 . Of the four MyTH4-FERM myosins expressed in humans, Myo7a is expressed in several tissues and localizes to inner ear stereocilia 12 , Myo7b is expressed in transporting epithelia and localizes to the tips of microvilli 13 , Myo15a is expressed in the inner ear and localizes to the tips of stereocilia 14 , and Myo10 is expressed in most cells and localizes to the tips of filopodia 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Myo10 is a member of a phylogenetically ancient group of myosins characterized by one or more MyTH4-FERM domains (Myosin Tail Homology 4 and band 4.1, Ezrin, Radixin, Merlin). The MyTH4-FERM myosins are strongly associated with protrusions based on actin bundles, such as filopodia, microvilli, and inner ear stereocilia 10 , 11 . Of the four MyTH4-FERM myosins expressed in humans, Myo7a is expressed in several tissues and localizes to inner ear stereocilia 12 , Myo7b is expressed in transporting epithelia and localizes to the tips of microvilli 13 , Myo15a is expressed in the inner ear and localizes to the tips of stereocilia 14 , and Myo10 is expressed in most cells and localizes to the tips of filopodia 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Myo7b, Myo7a, Myo10, and Myo15a also contain one or two MyTH4-FERM tandems in their tail domains (14). A common property of MyTH4-FERM myosins is their involvement in the formation or elongation/stabilization of actin-bundle supported structures, including filopodia, microvilli, and stereocilia (15). This property first appeared in ancient MyTH4-FERM myosins and is conserved over 1 billion y of evolution (14,16,17).…”
mentioning
confidence: 99%
“…It is located in the second FERM domain of the MYO15A protein. Previous reports suggested that the MyTH4-FERM domain is required for its localization to stereocilia tips and enriching the adhesion molecules, actin-regulatory proteins [ 23 ]. Mutations in this domain could also r result in losing the normal function of the MYO15A protein.…”
Section: Discussionmentioning
confidence: 99%